Dakwah Disabilitas: Majelis Da’i Muda (Mdm Bulukumba), Media Dan Anak Muda - Fathayatul Husna; Futri Syam; Dony Arung Triantoro; Raudhatun Nafisah; Muhibbul Subhi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The development of da'wah is increasing, including in South Sulawesi, especially Bulukumba. One of the pioneering da'wah organizations in Bulukumba is the Bulukumba Da'i Muda Council (MDM). Historically, MDM was founded on the desire and belief of the young preachers of Bulukumba to spread Islamic da'wah to all circles in South Sulawesi. There are 3 main targets of MDM in preaching: mothers, street youth and people with disabilities. This article is examined using several concepts, namely identity negotiation and expressing Islam. This study uses a qualitative approach with data collection techniques through in-depth interviews with research informants. The da'wah movement carried out by the Bulukumba Da'I Council (MDM) is inseparable from the portrait of contemporary issues, making youth and disabilities the primary targets for preaching. Da'wah activities among disabled people in South Sulawesi are new da'wah activities. MDM is a pioneer organization in this da'wah. The approach used in preaching is motivational and economical. In contrast, a dynamic approach is used among youths, namely, getting into the youth's habits, such as hanging out on beaches and cafes. These da'wah activities use thematic methods by raising material ranging from the Fiqhi of Worship to studying the interpretation of the Koran.